2010
DOI: 10.1111/j.1600-0609.2010.01443.x
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis in acute myeloid leukaemia patients receiving high‐dose chemotherapy: No impact of chitotriosidase and mannose‐binding lectin polymorphisms

Abstract: Infections after chemotherapy often cause significant morbidity in patients with acute myeloid leukaemia (AML). Chitotriosidase (CHIT) and mannose-binding lectin (MBL) are part of the innate immune system. Polymorphism in the CHIT-coding gene (CHIT1) may be associated with Gram-negative sepsis in children with AML, and polymorphism in the MBL-coding gene (MBL2) seems to modify the risk of infections in several patient groups. The purpose of this study was to investigate the possible associations between polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
4
15
0
1
Order By: Relevance
“…Another interesting analysis showed a trend toward more grade 4 neutropenic infections in multiple myeloma patients carrying the high MBL-producing wild-type exon polymorphism [14]. Interestingly, Klostergaard et al [48] found a significantly higher incidence of Gram-negative blood cultures in high MBL genotypes, which could explain why we found a higher incidence of febrile neutropenia in high MBL genotypes and positive blood cultures of only Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa) in our study.…”
Section: Discussionsupporting
confidence: 49%
“…Another interesting analysis showed a trend toward more grade 4 neutropenic infections in multiple myeloma patients carrying the high MBL-producing wild-type exon polymorphism [14]. Interestingly, Klostergaard et al [48] found a significantly higher incidence of Gram-negative blood cultures in high MBL genotypes, which could explain why we found a higher incidence of febrile neutropenia in high MBL genotypes and positive blood cultures of only Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa) in our study.…”
Section: Discussionsupporting
confidence: 49%
“…However our result inconsistent with study by Hellemann et al [31] in critically ill patients admitted to an intensive care, which reported an association of low MBL2 O/O genotype with an increased incidence of Gram-positive infections. Other study performed by Klostergaard et al [32] didn't find any association between MBL2 polymorphism and the type of bacterial sepsis. The diversity between the different studies may be explained by fact that MBL also acts as a scavenger molecule in maintaining internal tissue homeostasis.…”
Section: Discussionmentioning
confidence: 77%
“…However, correlation was determined between MBL-2 polymorphisms and the duration of febrile episodes in our study. Some studies found no differences between the frequency of infections and MBL-2 GPs (Frakking et al, 2009;Klostergaard et al, 2010). The second major part of our discussion is on the effect of MBL-2 variants on bacterial subclasses.…”
Section: Discussionmentioning
confidence: 83%
“…There are some articles that support the role of different GPs in FN (Vekemens et al, 2007). It is now nearly four decades since the relationship between the degree of neutropenia and the risk of bacterial and fungal infections was first recognized in patients treated for cancer (Bucaneve et al, 2005;Vekemens et al, 2007;Klostergaard et al, 2010;Roongpoovapatr and Suankratay, 2010). Infections were noted to be worse during relapse of the underlying disease and the failure of leukocytes to recover following an infection has a very poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation